The countermeasure for Zika virus: a hard nut to be cracked. (19th April 2018) - Usman, Sana; Naz, Zara; Saleem, Komal; Bashir, Hamid; Bilal, Muhammad; Sumrin, Aleena
The emergence of Zika virus (ZIKV) infection in America has caused a new threat worldwide, as it is linked with the increased incidence of congenital microcephaly in neonates and development of Guillain–Barré syndrome. A number of potential antiviral drugs such as sofosbuvir, BCX4430, NITD008 and 7-DMA have shown activity against ZIKV both in vitro and in vivo. Similarly, different research organizations and academic institutions are trying hard to develop a vaccine against the ZIKV. Some of these groups have received approval from the US FDA to start Phase I clinical trials. Immuno-based treatment strategies, such as use of humanized monoclonal antibodies (hE16 and CR4373) have also entered clinical trials. However, a licensed vaccine is still a long way off and efforts should be made to accelerate the evaluation procedures while minimizing the delay in licensing.